EFEKTIVITAS MODEL PEMBELAJARAN RME MENGGUNAKAN MEDIA MONOPOLI MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PADA MATERI PELUANG - Ahmad Fatikhul Udin (INSPIRAMATIKA, 2021)
This study aims to determine the effectiveness of the application of cooperative learning models with realistic mathematics education approaches using mathematical monopoly media to improve the ability to think creatively in learning opportunities in class VIII MTs Darul Ulum Pasinan. The study population was all students of class VIII-C MTs Darul Ulum Pasinan. Data was collected by using a learning completeness test, observation sheet of student activity, observation sheet of teacher activity, and student response questionnaire. The results of descriptive statistical analysis show: (1) the percentage of classical mastery learning is 88.89%, (2) the percentage of student activity is 89.1%, (3) the percentage of teacher activity is 90.5% and (4) the percentage of student response is 93.25%. From the results of this study it can be concluded that the application of the cooperative learning model with realistic mathematics education approach using mathematical media monopoly is effectively used to improve the ability to think creatively in learning opportunities in class VIII MTs Darul Ulum Pasinan.